Muscle Loss Is Associated with Overall Survival in Patients with Metastatic Colorectal Cancer Independent of Tumor Mutational Status and Weight Loss. (6th May 2021) - Best, Till Dominik; Roeland, Eric J.; Horick, Nora K.; Van Seventer, Emily E.; El‐Jawahri, Areej; Troschel, Amelie S.; Johnson, Patrick C.; Kanter, Katie N.; Fish, Madeleine G.; Marquardt, J. Peter; Bridge, Christopher P.; Temel, Jennifer S.; et al.
Abstract: Background: Survival in patients with metastatic colorectal cancer (mCRC) has been associated with tumor mutational status, muscle loss, and weight loss. We sought to explore the combined effects of these variables on overall survival. Materials and Methods: We performed an observational cohort study, prospectively enrolling patients receiving chemotherapy for mCRC. We retrospectively assessed changes in muscle (using computed tomography) and weight, each dichotomized as >5% or ≤5% loss, at 3, 6, and 12 months after diagnosis of mCRC. We used regression models to assess relationships between tumor mutational status, muscle loss, weight loss, and overall survival. Additionally, we evaluated associations between muscle loss, weight loss, and tumor mutational status. Results: We included 226 patients (mean age 59 ± 13 years, 53% male). Tumor mutational status included 44% wild type, 42% RAS‐mutant, and 14% BRAF‐mutant . Patients with >5% muscle loss at 3 and 12 months experienced worse survival controlling for mutational status and weight (3 months hazard ratio, 2.66; p < .001; 12 months hazard ratio, 2.10; p = .031). We found an association of >5% muscle loss with BRAF ‐mutational status at 6 and 12 months. Weight loss was not associated with survival nor mutational status. Conclusion: Increased muscle loss at 3 and 12 months may identify patients with mCRC at risk for decreased overall survival, independent of tumor mutational status. Specifically, >5% muscle loss identifies patients within each category of tumor mutational status with decreased overall survival in our sample. Our findings suggest that quantifying muscle loss on serial computed tomography scans may refine survival estimates in patients with mCRC. Implications for Practice: In this study of 226 patients with metastatic colorectal cancer, it was found that losing >5% skeletal muscle at 3 and 12 months after the diagnosis of metastatic disease was associated with worse overall survival, independent of tumor mutational status and weight loss. Interestingly, results did not show a significant association between weight loss and overall survival. These findings suggest that muscle quantification on serial computed tomography may refine survival estimates in patients with metastatic colorectal cancer beyond mutational status. Abstract : Cancer cachexia has traditionally been defined using weight loss; however, loss of skeletal muscle may be a more objective measure. This article reports the results of a retrospective study that assessed whether skeletal muscle loss is associated with overall survival in patients with metastatic colorectal cancer, independent of tumor mutational status and weight loss.